PENERAPAN PROFESIONALITAS GURU PENJASORKESDI SMP NEGERI KECAMATAN V KOTO TIMUR KABUPATEN PADANG PARIAMAN - Arisman Arisman (JURNAL PENDIDIKAN ROKANIA, 2017)
The purpose of this study was to determine the application to the professionalism of teachers in planning, implementation and evaluation of physical educationteaching done by the teachers of SMP di Kecamatan V Koto Timur. This research used descriptive research. The population of this study were all physical education teachers at SMP di Kecamatan V Koto Timur as much as 12 people. Sampling was used in total sampling. For data collection tool was used a questionnaire using Guttman Scale Models. Furthermore, the data was analyzed by using descriptive statistical techniques. The results were : 1)The level of achievement in terms of planning and learning process was in a bad level, with 64.6% of the respondents said the learning proces was implementedand 35.4% of the respondents said it was not implemented. 2) The level of achievement in terms of implementing the learning process in the classification ofperforming was in a bad level , with 58.7% of respondents said the learning process was implemented and 41.3% of respondents said it was not implemented. 3)The level of achievement in terms of evaluating the learning process of the classification in performing was in a bad level, with 59.1% of the respondents said the learning process was implemented and 40.9% of the respondents said it was not implemented.